Remodeling of cytoskeletal architecture of nonneuronal cells induced by synapsin. - Han, H Q (1994)
The synapsins, a family of neuron-specific phosphoproteins, have been implicated in the functional and structural maturation of synapses. The cell biological basis for these effects is unknown. In vitro, the synapsins interact with cytoskeletal elements including actin. To examine, in vivo, the possible effect of the synapsins on cytoskeletal organization and cell morphology, we have transfected each of the four known members of the synapsin family into nonneuronal cells. We report here that synapsin expression in fibroblast cells gives rise to an alteration in cell morphology that is associated with formation of highly elongated processes. This morphological change is accompanied by a reorganization of filamentous actin (F-actin) characterized by disruption of existing stress fibers and formation of bundles of actin cables in the elongated processes. These results suggest that interactions of the synapsins with actin, and possibly with other cytoskeletal elements, may play a role in the morphological differentiation of neurons.